Analisis Pendapatan Dan Strategi Pemasaran Buah Pedada (Sonneratia Caseolaris L) Menjadi Sirup Pedada (Studi Kasus: Jalan Bambu Kuning Kelurahan Selat Tanjung Medan Kecamatan Datuk Bandar Timur Kota Tanjungbalai) - Nilma Aprilia; Gustami Harahap; Rahma Sari Siregar (CULTIVATE: Journal of Agriculture Science, 2023)
This study aims to find out the income of business actors in the pedada syrup business and to find out the marketing strategy for pedada fruit to become pedada syrup in Jalan Bambu Kuning, Tanjung Selat Village, Medan, Tanjungbalai City. This type of research is descriptive with a qualitative approach, location determination is determined purposively (purposive), population and sample consist of 1 (saturated sample), data collection techniques used primary and secondary data, data analysis techniques namely income analysis and marketing strategy using 7P (marketing mix). The results of the research on pedada syrup business income per month are Rp. 2,674,376, Implementation of the 7P marketing strategy in terms of products, the product has a halal logo with a size of 550 ml. The price of chest syrup is Rp. 30,000/bottle. The marketing place is carried out at the home of the business actor. Promotion is simple, because on the bottle packaging only the cellphone number is printed. People in the pedada syrup business provide workforce training to expedite the production process. Physical Evidence, arrangement of products at business locations is structured and attractive. The production process is carried out according to the principles of sanitation and hygiene.